Fraud detection on canned tuna marketed in Brazil - Gambarini Ferri, Yete [UNESP]; Alves de França, Danilo [UNESP]; Piologo Ciciliato, Murilo [UNESP]; Pessoa Araújo, João [UNESP]; Vaz Rodrigues, Marianna [UNESP] (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2024)
Tuna provides a healthy diet, it’s rich on omega 3, high biologic value proteins, vitamins, and other nutrientes. The most popular presentation is in cans. Due to the fish’s high price however, frauds were reported taking advantage over other species with similar taste but lower cost on fish used for this purpose, reducing production cost, a commonly fact observed in tuna cans. Use of species not declared in the product label implies on fraud. Nowadays Brazilian legislation forecasts detection of fraud in food by molecular analysis in routine inspection. Thus, the study aimed to detect economic fraud through species substitution in canned tuna by means of conventional PCR technique associated with real-time PCR (qPCR). Among 47 analyzed samples merely 7 (14,89%) contained only tuna, 9 had low and 25 had high concentration of another fish, and 7 did not amplified tuna’s DNA, meaning there weren’t any tuna. The results show that economic fraud via non declared species exists with high percentage, showing that is important to install survaillance active, once consummer is being mistaking and this practice is crime according to Brazilian legislation. Another point is that qPCR technique can be used to detect this kind of crime, which present high sensitivity, specificity, fast execution and low cost.
Detecção de fraude em conservas de atum comercializadas no Brasil
Keywords: economic fraud; fish; forensic genetics; qPCR